Ileoileal intussusception secondary to angiofibrolipoma - Blaz Zavala, Rogelio A.; Pinto-Juarez, Karen J.; Ortiz-Vargas, Astrid; Osnaya-Garcia, Idalia A. (International Journal of Research in Medical Sciences, 2023)
Intussusception is an uncommon cause of intestinal occlusion in adults, accounting for 1-5% of the causes. In this group it is important to rule out malignant tumors as the primary cause of intussusception. This pathology is explained by the invagination of a segment of the intestine onto itself. The clinical manifestations are those typical of intestinal occlusion. Within the study protocol, the CT scan shows the target sign or sausage image depending on the slice. Surgical management will be necessary in order to re-establish intestinal transit and remove tumors. We present the case of a 45-year-old woman with upper intestinal occlusion secondary to ileoileal intussusception due to submucosal angiofibrolipoma.